Assessment of Metformin Floating Tablets: Natural-Synthetic Polymer Combinations as Excipients for Enhanced Formulation - Maikifi, S. A; Damodharan, N; Okpanachi G.O.; Oduola A. R (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2024)
This study focuses on optimizing a gastric floating tablet formulation designed specifically for Metformin HCl to improve the management of type 2 Diabetes Mellitus (DM). The formulation strategy combines natural and synthetic polymers, for a sustained-release (SR) prepared using wet granulation. The tablet contains Metformin HCl and a synergistic blend of sodium alginate and synthetic polymer (HPMC K4M). Methodological preparations involved rigorous evaluations to ensure adherence to required parameters. Results indicated that a batch with an HPMC K4M to sodium alginate (M7) ratio of 3:1 demonstrated optimal performance. Key findings included significant drug release, with over 90% of Metformin liberated within 8 hours in vitro, a swelling index exceeding 100% within 5 hours, and sustained buoyancy in simulated gastric fluid for over 10 hours. The integration of synthetic polymer enhances cost-effectiveness and reproducibility, while the natural polymer ensures biodegradability and reduces toxicity concerns. This optimized formulation of the Metformin floating tablet shows promise for further analysis and potential commercialization. Its attributes represent an advancement in type 2 DM management, providing favorable drug release kinetics and gastric buoyancy. Thus, it introduces a novel therapeutic approach to diabetes care.